The Role of Financial Literacy as a Mediator of The Influence of Financial Knowledge, Financial Attitude, Financial Experience, and Locus of Control on Students' Personal Financial Management - Anggraini Lokku Dapa Teo; Ahmad Mukoffi; Moch Nurhidayat (International Journal of Management and Business, 2026)
Personal financial management is an essential skill that students need to effectively organize and plan their finances. However, many students still struggle with financial management, which can lead to financial problems in the future. This study aims to analyze the role of financial literacy as a mediating variable in the relationship between financial knowledge, financial attitude, financial experience, and locus of control on students' personal financial management. This research employs a quantitative approach using a survey method on Management students at Universitas Tribhuwana Tunggadewi Malang from the 2021 and 2022 cohorts. Data were collected through questionnaires and analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results indicate that financial literacy has a significant influence on personal financial management and serves as a mediator in the relationship between independent variables and personal financial management. These findings have implications for students to enhance their financial literacy to better manage their finances and for educational institutions to improve financial literacy programs for students.